Cherenkov imaging for linac beam shape analysis as a remote electronic quality assessment verification tool. Issue 2 (14th December 2018) - Miao, Tianshun; Bruza, Petr; Pogue, Brian W.; Jermyn, Michael; Krishnaswamy, Venkataramanan; Ware, William; Rafie, Frank; Gladstone, David J.; Williams, Benjamin B.
Abstract : Purpose: A remote imaging system tracking Cherenkov emission was analyzed to verify that the linear accelerator (linac) beam shape could be quantitatively measured at the irradiation surface for Quality Audit (QA). Methods: The Cherenkov camera recorded 2D dose images delivered on a solid acrylonitrile butadiene styrene (ABS) plastic phantom surface for a range of square beam sizes, and 6 MV photons. Imaging was done at source to surface distance (SSD) of 100 cm and compared to GaF film images and linac light fields of the same beam sizes, ranging over 5 × 5 cm 2 up to 20 × 20 cm 2 . Line profiles of each field were compared in both X and Y jaw directions. Each measurement was repeated on two different Clinac2100 machines. An interreader comparison of the beam width interpretation was completed using procedures commonly employed for beam to light field coincidence verification. Cherenkov measurements are also done for beams of complex treatment plan and isocenter QA. Results: The Cherenkov image widths matched with the measured GaF images and light field images, with accuracy in the range of ±1 mm standard deviation. The differences between the measurements were minor and within tolerance of geometrical requirement of standard linac QA procedures conducted by human setup verification, which had a similar error range. The measurement made by the remote imaging system allowed for beam shape extraction of radiation fields at the SSD location of the beam. Conclusions: The proposed Cherenkov image acquisition system provides a valid way to remotely confirm radiation field sizes and provides similar information to that obtained from the linac light field or GaF film estimates of the beam size. The major benefit of this approach is that with a fixed installation of the camera, testing could be done completely under software control with automated image analysis, potentially simplifying conventional QA procedures with appropriate calibration of boundary definitions, and the natural extension to capturing dynamic treatment beamlets at SSD could have future value, such as verification of beam plans with complex beam shapes, like IMRT or "star‐shot" QA for the isocenter.